ENTREPRENEURIAL BEHAVIOR AMONG ECONOMIC EDUCATION STUDENTS - Enceng Yana (Cirebon International Conference on Education and Economics Proceeding, 2024)
Entrepreneurship is one of the distinguishing characteristics in the Economics Education Program at Universitas Swadaya Gunung Jati with the goal of producing outstanding entrepreneurs. This study aims to explore entrepreneurial behavior among students in the Economics Education Program at Universitas Swadaya Gunung Jati. The results of this research can provide insights for developing entrepreneurship programs tailored to their behaviors. The subjects of this study were active students in the academic year 2023/2024. Data were collected through interviews and observations. The research findings on students' entrepreneurial behavior indicate that psychological, social, and educational factors play crucial roles in influencing students' decisions to engage in entrepreneurial activities. The study found that intrinsic motivation, such as the desire to create something new and enhance independence, often serves as the primary driver behind students' decisions to start their own businesses. Universities should assist students in managing their time between running businesses and their academic activities.